All‐Direct‐Ink‐Writing of Artistic Supercapacitors: Toward On‐Demand Embodied Power Sources. (11th June 2022) - Lee, Seong‐Sun; Kim, Se‐Hee; Ahn, David B.; Lee, Kwon‐Hyung; Jo, Yejin; Jeong, Sunho; Lee, Sang‐Young
Abstract: Despite the extensive studies on printed power sources for user‐customized shape‐versatile electronics, most of them have still focused on printing of electrochemically active materials, with little attention to passive components such as current collectors and packaging, thus hindering their versatile application. Here, all‐direct‐ink‐writing (DIW) of artistic supercapacitors (ASCs) as a facile and scalable strategy to enable power source‐unitized monolithic electronic devices with various form factors is demonstrated. Interdigitated nickel current collectors embedded inside a polyurethane support layer are fabricated using DIW printing, which can facilitate the subsequent printing of multi‐scale, ultrathick electrodes. Interstitial voids between the DIW‐printed adjacent electrode layers are densely infiltrated by click‐crosslinkable electrolyte inks with well‐tuned rheological properties. The void‐free electrode/electrolyte assembly is conformally printed with a waterproof packaging ink to enable hermetic encapsulation, eventually producing all‐DIW‐printed ASCs with efficient space utilization, design diversity, and dimensional scalability. Notably, the resulting ASC can be seamlessly unitized with arbitrary‐shaped 3D objects (e.g., miniature pagodas), allowing for the potential development of on‐demand embodied power sources for electronic devices. Abstract : All‐direct‐ink‐writing (DIW) of artistic solid‐state supercapacitors (ASCs) is presented as a facile and scalable strategy to enable power source‐unitized monolithic electronic devices with various form factors. The resulting all‐DIW‐printed ASCs exhibit improvements in the design diversity, dimensional scalability, and seamless integration with complex‐structured 3D objects (e.g., miniature pagodas), allowing for the potential development of on‐demand embodied power sources.